1982
DOI: 10.1017/s0021859600031282
|View full text |Cite
|
Sign up to set email alerts
|

The effect ofRhizobiuminoculation on white clover in improved hill soils in the United Kingdom

Abstract: The benefits to establishment and growth of white clover cvs Aberystwyth S.184 and Grasslands Huia of inoculation with three strains of Rhizobium trifolii, using the peat or liquid inoculum techniques, were investigated during 1975-8 on improved hill soils ranging from brown earth through dry and wet peaty podzol to deep peat.Inoculation induced positive response in either number of seedlings, plant cover or dry-matter production in 18 out of 139 comparisons, had no effect in 118 and produced a negative respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The highly effective strains of clover rhizobia isolated in these studies may be useful in such inoculant selection programmes. These findings support the recommendation of Jones & Burrows (1969) and Newbould et al (1982) for the routine use of Rhizobium inoculants when sowing white clover, and also marsh trefoil in improved acid soils to maximize productivity from these pastures.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The highly effective strains of clover rhizobia isolated in these studies may be useful in such inoculant selection programmes. These findings support the recommendation of Jones & Burrows (1969) and Newbould et al (1982) for the routine use of Rhizobium inoculants when sowing white clover, and also marsh trefoil in improved acid soils to maximize productivity from these pastures.…”
supporting
confidence: 85%
“…Previous reports (Gibson et al, 1975;Sherwood & Masterson, 1974) have stressed the importance of using the correct host in assessing the effectiveness of indigenous rhizobia. The clover variety used in this study was Grasslands Huia, which is well suited to hill land conditions (Newbould et al, 1982), and the Lotus variety was G4705 (Grasslands Maku) which has shown potential in Scottish hill trials (Charlton, 1975). The rhizobia isolated using these host plants may not be representative of the soil population, but they do represent the strains which will form nodules on agricultural varieties of their particular hosts.…”
Section: Isolation Of Rhizobiamentioning
confidence: 99%
See 1 more Smart Citation
“…Effective rhizobia have been successfully introduced into UK low-fertility peat or peaty podzol soils where strains ineffective on white clover are widespread (Holding & King 1963). However, even on these soils responses to inoculation were inconsistent and only occurred where the inoculant strains form >50% of the nodules (Newbould et al 1982).…”
Section: Introduction Of Effective Rhizobiamentioning
confidence: 99%
“…Newbould et al 8 recorded a positive response in only 18 out of 139 comparisons made a different locations. Many of the hill soils of Britain are known to have deficient populations of rhizobia 1, 2, 3, 9,10 and yet commercial inoculation of white clover in hill reseedings is still uncommon.…”
Section: Introductionmentioning
confidence: 98%